Academic performance in polytechnic: The role of psychological capital and emotional intelligence - Nurbaya, Siti; Hasan, Halid; Octalina, Lydia Ery (Jurnal Penelitian, 2024)
This research aims to test whether psychological capital and emotional intelligence can influence academic performance in the context of the Business Administration Department. The population in this study was 120 students who had taken project management courses. A total of 92 samples were determined using the Krecjie Morgan table and using stratified random sampling techniques. The data collection method uses an offline survey and the data analysis method is carried out in two ways, namely descriptive analysis and inferential statistical analysis using the SPSS for Windows version 26 application. The results of the research show that psychological capital influences academic performance, emotional intelligence influences academic performance and Lastly, psychological capital and emotional intelligence simultaneously influence academic performance. To the Department of Business Administration and Malang State Polytechnic in general, project-based learning is a major requirement in vocational education institutions today considering the complexity of the business and industrial world which requires student skills in studying company culture.